Optimized fatigue performance of martensitic stainless steel AISI 440C using deep rolling integrated into hardening process - Donhongprai P.; Juijerm P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The deep rolling process can be modified by annealing at appropriate temperature and time to optimize the fatigue performance of metallic materials. The hardening process of the martensitic stainless steel AISI 440C composes of quenching and double tempering processes. We suggest to integrate the deep rolling process into the hardening treatment because the heat from the tempering process possibly provides sufficient static strain ageing effects. It was found that the deep rolling process can be integrated fully into the hardening process of the martensitic stainless steel AISI 440C, especially in the middle of the double tempering processes. The heat of the tempering process after the deep rolling process leads to beneficial static strain ageing effects as a consequence of greater fatigue lives. Moreover, the maximum fatigue life was detected in this research, when the optimized annealing had been performed instead of the second tempering process.